RETROSPECTIVE STUDY OF A SERIES OF 203 PATIENTS WITH TEMPOROMANDIBULAR JOINT DISORDERS PRESENTING AT SCHOOL OF DENTISTRY, UNIVERSITY OF SULAIMANI - Gaphor, Shanaz Mohammad; Abdullah, Mustafa Jamel (European Scientific Journal, ESJ, 2014)
Background: Temporomandibular Disorders (TMDs) constitute a complex and heterogeneous group of conditions and clinical problems that involve the temporomandibular joint (TMJ) and the masticatory musculature. TMD are an important challenge for dental profession because is a field of dentistry with many controversies in the aetiopatogenesis, diagnosis and treatment Objective: This study was designed to analyze 203 patients with temporomandibular joint disorders according to age, sex and possible etiological factors Method: A retrospective study was done among 203 patients attending School of Dentistry, University of Sulaimani, between January 2007 and December 2011. The age range was between 10-79 years. About 86 (42.36%) of patients were males and 117 (57.63%) were females. The male/female ratio was 0.73:1. Personal informations, including age, sex, reason for consultation, occupation as well as sign and symptoms, and possible etiological factors for temporomandibular joint disorder were registered. Chi Square test was used to analyze the data. Result: The most commonly affected age group was 20-29 and 30-39 year old (63.05, 13.30, respectively), temporomandibular joint disorders was more common among females (57.63%) than males (42.36%). Pain was the most common reason for consultation (53.18%), the majority of patients were student (64.03), the most common sign was clicking (77.83%), the most common etiological factors for temporomandibular joint disorders were habit (70.44%), followed by stress (44.33%) and abnormal occlusion (37.93%). Habit and stress were more common among females (73.50%, 45.29%, respectively) than males (63.95%, 43.02%, respectively) while occlusal abnormality was more common among males (40.69%) than females (35.89%). however sex differences for both males and females was not significant Conclusion: The authors concluded that the majority of patients with temporomamdibular joint disorders were young aged and females; etiology of temporomandibular joint disorders are multifactorial including habit, stress and abnormal occlusion; therefore treatment should be tailored for each patients accordingly, stress management interventions suggested to be beneficial in reducing the sign and symptoms of temporomandibular joint disorders